MENINGKATKAN KEMAMPUAN SISWA DALAM MENULIS TEKS DESKRIPSI DENGAN PENERAPAN MODEL PEMBELAJARAN TEAM GROUP TOURNAMENT - Annisa, Ervina Ervina (Linguistik : Jurnal Bahasa dan Sastra, 2023)
The use of Team Game Tournament learning model in the classroom is still rarely used in classes in Indonesia. However, this Classroom Action Research shows an increase in each cycle that occurs when conducting research. The purpose of this study was to determine the impact of using the TGT (Team Group Tournament) learning model to improve students' writing learning outcomes in English lessons.